Kepuasan Pasien Terhadap Kualitas Pelayanan Di Apotek Leontin Farma BSD Maret – April Tahun 2020 - Gina Aulia; Holidah Holidah; Liswati Friana Sipayung; Sheila Meitania Utami (STIKes Kharisma Persada, 2021)
A Drugstore is where the pharmacists practice as pharmaceutical service facility. Based on Indonesia government regulation no. 51, year 2009, Pharmaceutical services is a direct responsible services to the patience regarding pharmaceutical preparation. The purpose of this study is to determine of patient satisfactory regarding Pharmaceutical services based on reliability, responsiveness, assurance, empathy, and appearances dimension. The type of this research is a descriptive study by giving a questionnaire about the assessment patient satisfaction with pharmaceutical services to 100 respondents who came to Leontin Farma BSD drugstore with Quota Sampling technique. Based on results obtained 58% male patients. Most patient visits by age were 42-59 years as many as 35 patients. As for assessment system about description of patient satisfaction with pharmaceutical services based on the 5-dimensional questionnaire in the reliability section, 100% very satisfied; responsiveness, 100% is very satisfied; assurance,100% very satisfied; empathy, 100% very satisfied and appearance with 100% were very satisfied.Therefore, the results on patient satisfaction with pharmaceutical services at Leontin Farma the BSD drugstore in March-April 2020 are 100% with a very satisfied category. In the future hopefully the pharmacy officer can be more friendly with pharmaceutical services since can affects the quality of the drugstore.